When The Music Fails: The Impact of Service Recovery Strategies on Forgiveness and Behavioral Outcomes in the Concert Industry - Rana Nandita Shani; Gita Gayatri (Siber Nusantara Publisher, 2026)
Interest in music concerts in Indonesia continues to grow, which should be an important indicator for the creative industry to capitalize on the habit of young people who enjoy attending concerts as a business opportunity. However, in reality, the quality of service from concert promoters has not improved, as indicated by the increasing number of concert service failures. The main obstacle is how concert promoters can address the anger and disappointment of concertgoers by implementing service recovery strategies that can alleviate these negative emotions. This study aims to examine the effect of service recovery strategies implemented by concert promoters on customer forgiveness and the behavioral outcomes of audiences who experience service failures. The methodology used was a self-administered questionnaire distributed through social media. The study sample consisted of 266 respondents who had attended music concerts, fandom members, and had experienced concert service failures. Data were analyzed using PLS-SEM with the help of SmartPLS 3. The results showed that apologies and voice had a positive and significant influence on customer forgiveness, while compensation had no significant effect. Furthermore, customer forgiveness was shown to increase brand trust, repurchase intentions, and relationship reconciliation, also reduce negative word-of-mouth reviews. The study also showed that brand trust positively influenced repurchase intentions, while repurchase intentions reduced negative word-of-mouth reviews and increased relationship reconciliation.